1x+6+9+15=29

Simple and best practice solution for 1x+6+9+15=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1x+6+9+15=29 equation:


Simplifying
1x + 6 + 9 + 15 = 29

Reorder the terms:
6 + 9 + 15 + 1x = 29

Combine like terms: 6 + 9 = 15
15 + 15 + 1x = 29

Combine like terms: 15 + 15 = 30
30 + 1x = 29

Solving
30 + 1x = 29

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30' to each side of the equation.
30 + -30 + 1x = 29 + -30

Combine like terms: 30 + -30 = 0
0 + 1x = 29 + -30
1x = 29 + -30

Combine like terms: 29 + -30 = -1
1x = -1

Divide each side by '1'.
x = -1

Simplifying
x = -1

See similar equations:

| 9(m+1)=24 | | (H-6)+20=-4 | | y^2-20y=90 | | 25-d+2d-14= | | 3x+5=61 | | 4(3b-1)+6=5(b+4) | | 15a*15a+ab-6b*6b-2a*2a-5ab-2a*2a+4ab+b*b= | | 80=4(2x-3)+20 | | x(2x+1)=19 | | 6n-4=3n+8 | | 8x+11-3x=46 | | x-4/4-1=x-12/5 | | 1/2x-5=5/8x | | 4(5x+10)-16x+8=40 | | a+12-3a+4a-30= | | p*p-p*p*p*p-p*p*p+2p*2p*2p+4p*4p*4p*4p-3p*3p+3p*3p= | | x^2+0.03x-0.91=0 | | (12-x)(x+1)(x-1)=160 | | in(x)+in(2-x)=0 | | b/8-6=10 | | 7x-5=10+2x | | (100-10)*c=45 | | 5(8x-6)=34 | | y^2+100=0 | | -2(9x-7)+12=8 | | a/2+5=11 | | 100-10*c=100 | | 10+x=32-4 | | 3a+8b+7a-b= | | 15x-8-10x+6=53 | | 6g=17 | | 7x+4(3-5x)=0 |

Equations solver categories